2019
DOI: 10.3390/pharmaceutics11070307
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Artificial Gel Forming Bolalipids as Novel Formulations in Antimicrobial and Antifungal Therapy

Abstract: The alarming growth of multi-drug resistant bacteria has led to a quest for alternative antibacterial therapeutics. One strategy to circumvent the already existing resistance is the use of photodynamic therapy. Antimicrobial photodynamic therapy (aPDT) involves the use of non-toxic photosensitizers in combination with light and in situ oxygen to generate toxic radical species within the microbial environment which circumvents the resistance building mechanism of the bacteria. Hydrogels are used ubiquitously in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…It has also been demonstrated that bolalipid methylene blue aerogels in combination with antimicrobial photodynamic therapy are able to inhibit growth and kill Saccharomyces cerevisiae. The possibility of using these matrices as a drug delivery system was also confirmed by biocompatibility studies performed on the surface of the cosmic membrane, which showed that both proposed bolalipid formulations showed excellent biocompatibility and high solidification capacity under body temperature conditions [92].…”
Section: Mycosismentioning
confidence: 78%
See 1 more Smart Citation
“…It has also been demonstrated that bolalipid methylene blue aerogels in combination with antimicrobial photodynamic therapy are able to inhibit growth and kill Saccharomyces cerevisiae. The possibility of using these matrices as a drug delivery system was also confirmed by biocompatibility studies performed on the surface of the cosmic membrane, which showed that both proposed bolalipid formulations showed excellent biocompatibility and high solidification capacity under body temperature conditions [92].…”
Section: Mycosismentioning
confidence: 78%
“…Thus, these hydrogels with incorporated amphotericin B may potentially be effective local antifungal therapy [91]. Other studies show that hydrogels can also become helpful tools supporting the action of photodynamic therapy of fungal infections, which is an effective way to treat infections caused by drug-resistant microorganisms [92]. This therapy involves the use of non-toxic photosensitizers in combination with light and oxygen in situ to create free radicals that are toxic to microorganisms [93].…”
Section: Mycosismentioning
confidence: 99%
“…HEPES (20 mM, pH 7.4) served as a negative control, sodium dodecyl sulfate (SDS) 1% (m/m) and 0.1 N sodium hydroxide were used as positive control. The determination was based on stereomicroscopic images taken with a Moticam 5 MP digital camera (Motic Deutschland GmbH) and an irritation score ( IS ), which included an assessment of haemolysis ( H ), vessel lysis ( L ), and blood coagulation ( C ) [ 37 ]. Events were photographed at the time of their occurrence and the irritation score was calculated as follows according to the literature [ 38 ]: …”
Section: Methodsmentioning
confidence: 99%
“…This therapeutic modality uses photosensitizers, light, and oxygen to disable the resistance-building capability of bacteria. In 2019, Goergen et al used single chain BAs as a gelating agent (Goergen et al, 2019 ) The BAs used by Goergen feature a 32-carbon central hydrophobic domain linked by either two phosphocholine or two dimethylphosphoethanolamine head groups. The BAs were co-formulated with methylene blue–a photosensitizer.…”
Section: Hydrogels Containing or Derived From Bolaamphiphilesmentioning
confidence: 99%